2023
DOI: 10.17507/tpls.1304.10
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and Challenges of eLearning Before and After the COVID-19 Pandemic: Faculty and Student Perceptions in Saudi Education

Abstract: Novelty and Topicality: The COVID-19 pandemic significantly affected the education sector, with eLearning transforming the global education system. Research Purpose: This study sheds light on how the English departments of King Khalid University overcame the pandemic’s impact, with respect to the shift to online learning. Motivation for the Study: The findings of the present study are of great importance for transforming the education system, not only in Saudi Arabia but worldwide. The globalization of educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Even though the viewer statistics on Panopto were more positive around the lectures where questions were embedded, none of the students attempted the embedded quiz through the streaming link, even though, according to the logs, the video itself was downloaded. There could be multiple reasons for downloading rather than streaming engagement, one of which could be limited access to the internet, particularly for students based overseas, which was noted as a frequent issue in the literature (Simonova, Faltynkova & Kostolanyova 2023;Tian & Lu 2022;Weng, Ng & Chiu 2023;Alhaider & Nisa 2023). Regardless of the cause behind the student activity, examining the Panopto statistics indicates that these efforts to improve student engagement were unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though the viewer statistics on Panopto were more positive around the lectures where questions were embedded, none of the students attempted the embedded quiz through the streaming link, even though, according to the logs, the video itself was downloaded. There could be multiple reasons for downloading rather than streaming engagement, one of which could be limited access to the internet, particularly for students based overseas, which was noted as a frequent issue in the literature (Simonova, Faltynkova & Kostolanyova 2023;Tian & Lu 2022;Weng, Ng & Chiu 2023;Alhaider & Nisa 2023). Regardless of the cause behind the student activity, examining the Panopto statistics indicates that these efforts to improve student engagement were unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…As Lin, Wu, and Lee note, 'Although online learning environments have advantages for learning, they need extra support to help students concentrate on learning' (2022: 156). Online learning poses challenges for students who may not have any previous experience of a level of independent learning with expectations of unsupervised work like take home essays and self-directed study towards lecture content (Ng, Ching & Law 2023;Alhaider & Nisa 2023;Bao 2020;Trenholm et al 2019). Furthermore, there are the challenges specific to online learning from other countries.…”
Section: Methodological Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of the advantages and challenges of DL before, during and/or after the COVID-19 pandemic were made by some studies as teaching and learning the four English language skills before and during the COVID-19 as perceived by EFL faculty and students (Alhaider & Nisa, 2023); Saudi EFL students' use and perceptions of blackboard before and during online learning (Alsuhaibani, 2021); synchronous and asynchronous English writing classes (Bin Dahmash, 2021); Saudi students' views of teaching English speaking online versus F2F during COVID-19 (Alzamil, 2021); distance education in higher education in Saudi Arabia in the post-COVID-19 Era (Alghamdi, El-Hassan, Al-Ahdal & Hassan, 2021); and educated Arabs' reading interests and preferences before, during and after the pandemic (Al-Jarf, 2022d). The literature review revealed lack of studies that probed students and teachers' attitudes towards DL four years after the emergency shift from F2F to DL that took place back in March 2020.…”
Section: Introductionmentioning
confidence: 99%